Mental Health and Access to Active Labor Market Programs - Bråthen, Magne; van der Wel, Kjetil A.; Løyland, Borghild (Nordic Journal of Working Life Studies, 2020)
This paper examines the often-overlooked precondition for successful implementation of active labor market policy, namely equal access to labor market programs. Focusing on a cohort of social assistance recipients, we compare program participation between individuals who were eligible for vocational training and had reported psychological distress, to possible participants with other health or social challenges. The study covers a period of six years. The results indicate that social services prioritize training for those without mental health problems. This is true independently of observed differences between the two groups in terms of demographic and human capital characteristics, work motivation and self-efficacy. Hence, the study concludes that there seems to be a mental health access bias in program participation among disadvantaged groups. Policy makers and future research should address possible organizational barriers to equal program access